PASTEURISASI SUSU MENGGUNAKAN GELOMBANG MIKRO UNTUK MENINGKATKAN MUTU PRODUK UMKM âNATURAL PROBIOTIKâ - Najmina, Raisa L. (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Milk can deteriorate fast since milk contains high nutrient contents such as lactose, fat, protein and pH of milk is close to neutral pH which very suitable for the growth of microorganisms. Pasteurization is used to kill all pathogen and mostly spoilage bacteria, and degradate enzymes. âNatural Probioticâ is a home industry in field milk production in Malang region, it still using conventional methods in milk pasteurization, heating process using fire from stove. âNatural Probioticâ have problem on pasteuritaion process, this problem influence milk pasteurized as raw material for milk product, which produce low quality of yoghurt and kefir. It can identified how to design a milk pasteurizer machine that simple and user friendly. The purpose of this program was to solve the UMKM âNatural Probioticâ problem on the quality of milk product using Wave Pasteurization Control (WPC) which is a simple machine, user friendly and efficient in pathogen and spoilage bacteria killing, enzyme inactivation, minimize protein denaturation. WPC developed continuously operating heat treatment, capable of controlling milk flow during heat treatment in spiral glass. The Mechanism of WPC used HTST system with temperature 72Â°C collecting with spiral glass as milk low in microwave, it is make even heating. Milk heating by microwave results from the conversion of microwave energy into heat by friction of water vibrating due to rapid fluctuation in the electromagnetic field. Experiment result showed that pasteurization milk using WPC gave TPC content 104cfu/ml, negative E. coli. WPC be able to increase profit Rp 8.676.450,00 with R/C Ratio 1,31. It concluded that WPC effectife for killing pathogen and spoilage bacteria, minimize denaturation of protein and gave improvement on milk product quality, productivity of yoghurt and kefir and profit of UMKM âNatural ProbioticKeywords:microwave, milk pasteurized, spiral glass